High prevalence of medication use in professional football tournaments including the World Cups between 2002 and 2014: a narrative review with a focus on NSAIDs - Tscholl, P. M.; Vaso, M.; Weber, A.; Dvorak, J. (British Journal of Sports Medicine, 2015)
The use of medication in international football has been monitored since the 2002 FIFA World Cup. Team physicians were asked to provide information on prescribed medication 72 h prior to each match for every player. 69% of adult male players reported using medication, with more than half the players using non-steroidal anti-inflammatory drugs (NSAIDs). Up to one-third of all players used NSAIDs prior to every match, regardless of whether they took the field or not. The mean intake of medication was significantly higher during the FIFA Women's World Cup (0.85 vs 0.77 substances per player and per match in men, p<0.001), whereas the use of NSAIDs was similar to that for men. In the Under-20 and Under-17 male competitions, the use of medication was lower as 60% of players used some kind of medication and 43% of the players used NSAIDs during the tournaments. Despite the potential side effects of medication, especially of NSAIDs in the recovery process after a sports activity, there is no evidence of decreasing intake. The reported incidence is alarming, and moreover is most probably underestimated, since self-medication by the players or treatment already prescribed by club physicians is not included in the published reports. Future studies should focus on the daily dosage, time of treatment and especially the medical indication for painkilling agents to better understand the underlying factors.